2020
DOI: 10.21203/rs.3.rs-52307/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxysterols Present in Alzheimer’s Disease Braininduce Synaptoxicity by Activating Astrocytes: A Major Role for Lipocalin-2

Abstract: Background: Among Alzheimer’s disease (AD) brain hallmarks, the presence of reactive astrocytes was demonstrated to correlate with neuronal loss and cognitive deficits. Evidence indeed supports the role of reactive astrocytes as mediators of changes in neurons, including synapses. However, the complexity and the outcomes of astrocyte reactivity are far from being completely elucidated. Another key role in AD pathogenesis is played by alterations in brain cholesterol metabolism. Oxysterols (cholesterol oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
(126 reference statements)
2
0
0
Order By: Relevance
“…We propose that the downregulation of GLT-1 and GLAST due to high levels of 27-OH plays an important role in this aberrant phenotype. The impact of 27-OH on astrocytes, including their activation and induction of sterile inflammation, aligns with the stress signals identified for both neurons and astrocytes by our group Loera-Valencia et al, 2021a) and others (Staurenghi et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We propose that the downregulation of GLT-1 and GLAST due to high levels of 27-OH plays an important role in this aberrant phenotype. The impact of 27-OH on astrocytes, including their activation and induction of sterile inflammation, aligns with the stress signals identified for both neurons and astrocytes by our group Loera-Valencia et al, 2021a) and others (Staurenghi et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, RxRγ induces the transcription factor REST in 2D primary cultures treated with 27-OH (Merino-Serrais et al, 2019), but mRNA levels were like controls in our 3D co-cultures, and the dendrite growth of its neurons was indeed compromised, which suggests that early 27-OH induced alterations in RxRγ signaling are sufficient to induce neuronal and astrocytic effects observed in this study. Our results also suggest a potential link between astrocytic function and the cognitive deficits observed in AD since the impact of 27-OH on astrocytes, including their activation and induction of sterile inflammation, aligns with the stress signals identified for both neurons and astrocytes Loera-Valencia et al, 2021a;Staurenghi et al, 2021). These findings imply a broader role for oxysterols such as 27-OH in disrupting astrocyte synaptic function, with implications for cognitive function and neurodegeneration.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have reported that LCN2 protein is secreted by neurons (Jha et al, 2015;Nagase and Tohda, 2021) and glial cells (Bi et al, 2013;Jang et al, 2013;Staurenghi et al, 2021;Weng et al, 2021). To determine the cellular distribution of LCN2 protein in the ACC of mice, we detected LCN2 by immunofluorescence staining and found that it mainly co-localized with neurons, and to a small extent with microglia and astrocytes in the ACC of naïve mice (Figures 5A, B).…”
Section: Lcn2 Expression Is Increased In the Acc After Sni 2wmentioning
confidence: 97%
“…Lipocalin-2 protein is secreted from neurons (Jha et al, 2015;Nagase and Tohda, 2021) as well as glial cells (Bi et al, 2013;Jang et al, 2013;Staurenghi et al, 2021;Weng et al, 2021). In order to explore whether up-regulation of LCN2 in the ACC is involved in the generation of chronic pain, we next constructed generated a broad-spectrum virus expressing short hairpin RNAs (shRNAs) to knock down LCN2 expression.…”
Section: Lcn2 Expression Is Increased In the Acc After Sni 2wmentioning
confidence: 99%
See 1 more Smart Citation